E-sports as a tool for (re)socialization - Mirontsov, Igor V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
This article examines the influence of e-sports in general and computer games in particular on the process of players’ socialization. Based on the theoretical analysis and the results of a series of expert interviews with managers of e-sports teams, players, journalists, professional psychologists, etc., it was concluded that there are three possible points of view on given question, and the advantages and disadvantages of each are shown in this paper.